Biomonitoring of atmospheric trace elements in agricultural areas and a former uranium mine - Rodriguez, Judith Hebelen (2014)
Most biomonitoring studies worldwide have evaluated the air quality in industrial and urban areas, and even in mining areas to a lesser extent. However, air quality investigations in agricultural areas are scarce. In the present study, the trace metal accumulation and physiological response of the biomonitor Tillandsia capillaris were assessed. Plant samples were transplanted to a reference site, a former open-cast uranium mine, and agricultural sites with varying pollution levels (from normal agricultural practices and near an open rubbish dump) in the province of Córdoba, Argentina. Biomonitors were exposed to ambient air for different exposure periods for physiological or trace element determination. The bioindicators revealed that the highest physiological damage occurred at the sites close to the open dump and the former uranium mine, while a comparison among exposure periods indicating the winter season produced the highest physiological damage in the biomonitor due to the adverse climatic conditions and air pollution. As the trace metal accumulation in the biomonitor was mainly associated with the open dump and uranium mine sites, monitoring and remediation programs should now be applied to these sites in order to alleviate the negative effects of pollution on the environment and the population.